Frequency of Subclinical Hyper and Hypothyroidism - Shah, Syed Iftikhar Ali (International Journal of Pathology, 2019)
Introduction: Thyroid disorders are one of the commonest endocrine diseases. Subclinical thyroid dysfunction is a laboratory base diagnosis and patients may be asymptomatic. However, later on it can lead to some serious health problems. The purpose of this study is to assess the frequency of subclinical hypo and hyperthyroidism in a population of patients presenting to the private clinic.Patients and Methods: This descriptive study was carried out in a private clinic in Peshawar between 2007 and 2012. The patients of all age groups, regardless of gender were selected by non-probability, random sampling technique. These patients presented with non-specific symptoms such as palpitation, constipation and generalized body aches. The findings of history, clinical examination and lab investigation of thyroid function were recorded and analyzed in SPSS v19.Results: Out of 4198 patients 3229(76.92%) were female and 969 (23.08%) were male. Both in male and female population, most of the patients belonged to middle age group i.e. 25 to 44 years. Among male patients 117 (12%) were hyperthyroid and 51 (5%) were hypothyroid. Sixty-nine patients (7%) were found in each category of Subclinical hyperthyroidism and hypothyroidism. Similarly, regarding female population, hyperthyroidism was detected in 505 (16%), hypothyroidism in 182 (6%), subclinical hyperthyroidism in 211 (7%) and subclinical hypothyroidism in 260 (8%) patients.Conclusions: Subclinical thyroid dysfunction is detected in substantial numbers in all the age groups. These patients should be monitored for complications of thyroid diseases, and patients with nonspecific symptoms and known risk factors should be evaluated for subclinical hypo or hyperthyroidism.